PREDIKSI KEGAGALAN USAHA KECIL DAN MENENGAH (UKM): SEBUAH PERSPEKTIF KEUANGAN - Sunarjanto, Nekhasius Agus; Roida, Herlina Yoka; Widyaningdyah, Agnes Utari (Universitas Nusantara PGRI Kediri, 2016)
Dentification of business failure is one in applying an early warning system for business activities in any scale. This identification is often run by banks to detect potential bankruptcy of a business who is given credit by banks. This study identifies the failure of SME businesses with financial approaches, using binomial logistic regression discriminant analysis. The results showed that the variable working capital / total assets, current assets / current liabilities, and quick / Inventory can predict the failure of the business (financial distress). The financial difficulties of the measured ability of SMEs in obtaining access to short-term loans. As a result, SMEs have difficulty in gaining access to loans from financial services, such as banking